Korelasi antara Strategi Nilai-Nilai Pendidikan Karakter Religius dengan Terbentuknya Akhlaq dalam Diri Siswa - Ahmad Afghor Fahruddin; Moh. Syamsi (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2020)
This paper will discuss the relationship between the values of religious character education strategies with the formation of morality in students. The type and approach in this research uses descriptive qualitative. In the current era of globalization, people ranging from adolescents, adults and even the elderly and most importantly to parents must be prepared to receive positive and negative impacts in the times, because we can access various information both nationally and internationally very young and fast. To deal with all this, the world of education prioritizes in terms of what strategies can instill the values of religious character education that focus on the formation of morality in students. In implementing the strategy of religious character education values the principal must apply important points such as strategy, educational values, religious character and morality.